Experiences of using “drunk glasses” in DWI-prevention campaigns (Academic Journal of Internal Affairs, 2011)
Drunk driving presents a daily problem all over the world. Reducing the number of accidents caused by drivers under the influence of alcohol is a vitally important task for the Hungarian Police as well. Sanctioning and prevention are the two basic tools for fighting this damaging and dangerous phenomenon. Traffic specialists of the police are continuously working on new methods for prevention. The article describes a new tool: “drunk glasses”; an excellent instrument for illustrating for sober subjects the influence of alcohol on the human body and on driving capabilities.
Keywords: drunk driving; simulation glasses; traffic safety